(untitled) (Research, Society and Development, 2022)
The objective was to investigate the prevalence of depressive signs and symptoms among undergraduate students of courses in the health area, at a Federal University, with a pedagogical curriculum project based on Active Teaching-Learning Methodologies, in a municipality in the interior of northeastern Brazil. This article is a cross-sectional and observational study with an analytical, descriptive, and quantitative approach was carried out by through self-administered semi-structured questionnaires. The subjects of this study were undergraduate students enrolled in eight courses in graduation on health sciences. This research was executed between February 2018 and June 2019. Quantitative data were processed using Excel software (Microsoft®) descriptively. The central influences of the tutorial module were anxiety (77%; n=314), sleep disturbances (79%; n=323), competitiveness (66%; n=271), individualism (60%: n=244) and stress (83.7%; n=343); other modules obtained smaller proportions. About 36% would change teaching institution, 44% would change course; Approximately 31% (n=129) of the students had at least one reported morbidity. Common Mental Problems were the most prevalent reported morbidity group (49%; n=63). The Beck Inventory identified that 35% (n=143) of the participants had some degree of depression; 2% (n=8) self-rated their health as ’poor/very bad’; 8% (n=33) reported using medication. The group of chemical substances most frequently used were psychotropic drugs, with emphasis on anxiolytics (43%; n=18) and antidepressants (29%; n=12); 45% (n=20) related to the use of medication to entering the University. We understand that an institutional, student, and teacher reflection on the applicability of MAEA should be considered.